2005
DOI: 10.1007/s11302-005-0648-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationships of dinucleotides: Potent and selective agonists of P2Y receptors

Abstract: Dinucleoside polyphosphates act as agonists on purinergic P2Y receptors to mediate a variety of cellular processes. Symmetrical, naturally occurring purine dinucleotides are found in most living cells and their actions are generally known. Unsymmetrical purine dinucleotides and all pyrimidine containing dinucleotides, however, are not as common and therefore their actions are not well understood. To carry out a thorough examination of the activities and specificities of these dinucleotides, a robust method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(141 citation statements)
references
References 28 publications
1
130
0
Order By: Relevance
“…This occurred despite a fall in GFR and suggested that proximal tubular reabsorption was markedly reduced [353]. Ap 4 A can stimulate a number of P2 receptor subtypes, including P2Y 1 and P2Y 4 receptors [331,410], which are both expressed in the rat proximal tubule (P2Y 1 apically, P2Y 4 basolaterally); intravenous delivery of the agonist does not allow differentiation between these possibilities.…”
Section: Renal Tubulesmentioning
confidence: 96%
“…This occurred despite a fall in GFR and suggested that proximal tubular reabsorption was markedly reduced [353]. Ap 4 A can stimulate a number of P2 receptor subtypes, including P2Y 1 and P2Y 4 receptors [331,410], which are both expressed in the rat proximal tubule (P2Y 1 apically, P2Y 4 basolaterally); intravenous delivery of the agonist does not allow differentiation between these possibilities.…”
Section: Renal Tubulesmentioning
confidence: 96%
“…INS45973 is an agonist of P2Y2/P2Y4 receptors, while INS415 is an agonist of P2Y2/ P2Y6 receptors. 19 …”
Section: Reagentsmentioning
confidence: 99%
“…Abbreviations: AR-C67085MX, 2-(propylthio)-β,γ-dichloromethylene-ATP; MRS2179, N 6-methyl-2′-deoxyadenosine-3′,5′-bisphosphate; RB2, Reactive blue 2. Note: Ap 4 A also activates various P2X receptors and the rat P2Y 4 receptor (Wildman et al 2003), but not the human P2Y 4 receptor (Shaver et al 2005). Suramin is known to inhibit G proteins and other intracellular targets.…”
Section: Figmentioning
confidence: 99%